THE BODY AND VOICE OF CHINESE WOMEN IN YUSIANA BASUKI'S NOVEL NAGA KUNING: A POSTMODERN FEMINIST HELENE CIXOUS - Satriani, Irma (Journal of Language, Literature and Teaching, 2025)
This study aims to analyse the representation of the body, trauma, and voice of Chinese women in Yusiana Basuki's novel Naga Kuning using Helene Cixous' postmodern feminist theory. Set against the backdrop of the May 1998 riots, this novel narrates women's bodies as spaces of historical wounds and sources of symbolic resistance. Through Cixous' concept of ecriture feminine, the writing of women's bodies is a strategy of resistance against patriarchal language. This study applies qualitative descriptive methods with close reading to analyse symbols, bodily metaphors, and linguistic rhythms that describe women's experiences as subjects who write themselves. The results show that the body in Naga Kuning represents the trauma of sexual violence and ethnic Chinese, as well as the local transformation from an object of power to a powerful subject through writing the body. The poetic, fragmentary, and emotional language in this novel reflects the practice of ecriture feminine, which liberates women's voices from phallocentric hegemony. This novel presents the female body as an aesthetic and political space for healing, memory, and post-traumatic identity formation.